Multiple Intestinal Erosions as a Result of Hemorrhage due to Parasites: Case Reports and Review of the Literature - Pitanga Lukashok, Hannah (Hindawi Publishing Corporation, 2011)
Obscure gastrointestinal bleeding appears to be uncommon in patients with parasites. In spite of that some reports had described this relationship in patients evaluated during capsule endoscopy procedures; the characteristic of the bleeding lesions remains unclear. This paper describes two patients with a massive obscure gastrointestinal bleeding due to ascariasis, using the new capsule endoscopy technology “MiroCam”, describing the characteristic of the lesions found in our patients (observed in a better image quality), and reviewing the literature.